Evaluation of a large-scale quantitative respirator-fit testing program for healthcare workers: survey results - Wilkinson, Irene J; Pisaniello, Dino; Ahmad, Junaid; Edwards, Suzanne (Infection control and hospital epidemiology, 2010)
To present the evaluation of a large-scale quantitative respirator-fit testing program. Concurrent questionnaire survey of fit testers and test subjects. Ambulatory care, home nursing care, and acute care hospitals across South Australia. Quantitative facial-fit testing was performed with TSI PortaCount instruments for healthcare workers (HCWs) who wore 5 different models of a disposable P2 (N95-equivalent) respirator. The questionnaire included questions about the HCW's age, sex, race, occupational category, main area of work, smoking status, facial characteristics, prior training and experience in use of respiratory masks, and number of attempts to obtain a respirator fit. A total of 6,160 HCWs were successfully fitted during the period from January through July 2007. Of the 4,472 HCWs who responded to the questionnaire and were successfully fitted, 3,707 (82.9%) were successfully fitted with the first tested respirator, 551 (12.3%) required testing with a second model, and 214 (4.8%) required 3 or more tests. We noted an increased pass rate on the first attempt over time. Asians (excluding those from South and Central Asia) had the highest failure rate (16.3% [45 of 276 Asian HCWs were unsuccessfully fitted]), and whites had the lowest (9.8% [426 of 4,338 white HCWs]). Race was highly correlated with facial shape. Among occupational groups, doctors had the highest failure rate (13.4% [81 of 604 doctors]), but they also had the highest proportion of Asians. Prior education and/or training in respirator use were not associated with a higher pass rate. Certain facial characteristics were associated with higher or lower pass rates with regard to fit testing, and fit testers were able to select a suitable respirator on the basis of a visual assessment in the majority of cases. For the fit tester, training and experience were important factors; however, for the HCW being fitted, prior experience in respirator use was not an important factor.